A comparative study of local governments in the constitutions of selected EU countries and Turkey - (:unkn) unknown (IGI Global, 2016)
In the effort to examine local governments within a country, the first place to look at would be the constitution of that state. Constitutions usually provide us with important information about local governments; on their types, competencies, revenues and various other characteristics. This study aims to compare the clauses devoted to local governments in the constitutions of 23 European Union (EU) member states and Turkey. While there are certain studies concerned with how local governments are worded within constitutions, these are generally singular cases focusing on one country alone. This chapter aims to provide comparative and informative information on local governments in the constitutions of the related states by categorizing the most commonly stipulated clauses. © 2016 by IGI Global. All rights reserved.